Pemberdayaan Pemuda Melalui Pembentukan Karang Taruna Dusun Di Desa Sumberbanjar - Lathif, Sahro Wardil; Fithrotin, Fithrotin; Amanullah, Ahmad Syahroni (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The youth generation has an important role in the process of developing a good nation, especially in the fields of education, religion, and social life. To make this happen, there needs to be a forum that is able to become a space for youth to move, one of which is youth organizations. The youth organization is a forum for young people to make progress in the local village. In addition, youth organizations have a strategic position and are urgently needed to answer social problems and sharpen the creativity of the youth of Sumbergondang Hamlet and Sumberbanjar Village. The problems that occur are very diverse, starting from the lack of concern for youth towards the Youth Organization, which caused the Youth Organization to decline for several years so that there was no improvement in the quality of youth in the village. The purpose of this service is to arouse youth interest in organizing so that the organization can run well, youth can unite, and members can become more structured and registered. The service method used is participatory action research (PAR), with the results of the service showing the success of rebuilding the Sumbergondang Hamlet Youth Group, which had been vacuumed.